Sosialisasi Pajak sebagai Penguat Kepatuhan Wajib Pajak di Tanjung Pinang - Teddy, Haryadi; Yusyawiru, Nurul; Rikayana, Hadli Lidya; Yusrizal; Adiman, Raja Multi Konvokesen (SAFE-Network, 2025)
This study explores the factors influencing tax compliance among Micro, Small, and Medium Enterprises in Tanjungpinang, specifically focusing on financial conditions, tax sanctions, and the role of tax socialization. The research aims to understand how these factors affect MSMEs' compliance with tax regulations. A survey was conducted with MSME owners in Tanjungpinang using a questionnaire to gather data on their financial conditions, knowledge of tax obligations, and perceptions of tax sanctions. The results indicate that financial conditions do not have a significant impact on tax compliance. However, tax sanctions are found to significantly encourage compliance, highlighting their role as a motivating factor for MSMEs to fulfill their tax obligations. Furthermore, the study reveals that tax socialization moderates the relationship between financial conditions and tax compliance, as well as between tax sanctions and compliance. Effective tax socialization strengthens the impact of both financial conditions and sanctions on compliance. The findings suggest that improving tax education and communication can play a crucial role in increasing tax compliance in the MSME sector, even in the face of financial challenges. This research provides valuable insights for policymakers to design more effective tax policies targeting MSMEs.